Steps and Customs Related to Stones of Jizzah Oasis - Rakhmanova Sokhiba Janzakovna (Global Scientific Publishing, 2022)
In this article, the role of the forty sacred sites in the Jizzakh region of the Republic of Uzbekistan in the history of mankind is discussed
Keywords: historical heritage left; the implementation; own holy shrines